EDUCATIONAL MANAGEMENT MODEL AT SMP BP AMANATUL UMMAH AND EDUCATIONAL MANAGEMENT STRATEGY AT SMP BP AMANATUL UMMAH - Ismail Antu; Vierna Nurihza Salsabila; Nasehatus Solehah; Ari Kartiko (Media Inovasi Pendidikan dan Publikasi, 2023)
Education is a guidance given by adults to immature children to achieve a goal, namely maturity. Educate and education are two things that are related. So that it can be concluded from these opinions that education is a conscious effort, not a haphazard act just so that one becomes an adult who is responsible and independent. This journal focuses on discussing the Education Management Model at SMP BP Amanatul Ummah and Education management strategies at SMP BP Amanatul Ummah. As well as this research is a qualitative study of the literature, namely theoretical studies, references and other scientific literature related to culture, values ​​and norms that develop in the social situation under study. The results of the education management model and management strategy have met the criteria for educational standards.